Experimental Study on Lateritic Soil Stabilization with Waste Engine Oil and Lime - et. al., Jayaprakash M C, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The world wide concern for cleanup, protection and enhancement of the environment has development of a sub discipline within the field of geotechnical engineering; namely Geoenvironmental, which is concerned with the application of geotechnical engineering to environmental control. It is within this area that the concepts of stabilization, solidification, reuse and recycling wastes in geotechnical engineering works are popularly encountered. The cost of the construction materials has rapidly increased and hence stabilization of soil using admixtures becomes Cost effective and eco-friendly blocks. Thus waste engine oil and natural lime considerably promise to reduce the cost of construction or alternative material that would be suitable for construction activities and also reduces the disposal problem and hence reduces contamination of soil and water.